Relationship between water supply and the occurrence of diseases in indigenous people in the state of Maranhão, Brazil (Research, Society and Development, 2020)
Water becomes a condition of risk to the health of indigenous peoples at the time when there are no surveillance and public policies that include measures to guarantee its quality. Therefore, the objective of this work was to evaluate the relationship between water supply and the occurrence of diarrhea cases in the Araribóia indigenous land, located in the State of Maranhão, Brazil. Studies were carried out in the villages covered by the Special Indigenous Sanitary District - DSEI-MA, with the main focus being the villages of the base of wire, where the direct relationship between the implementation of the water supply system and the improvement of health was observed of the population of these communities. The relationship was based on the occurrence of diarrhea cases registered in the period 2010-2017. The results revealed that the cases of diarrhea in the indigenous population of the Arame base pole registered in 2017 decreased by more than 78%, when compared to the year 2010, due to a 51.2% increase in access to drinking water and quality by indigenous people. However, there is a need for investments in the area of basic sanitation for indigenous communities, in order to prevent many diseases from affecting the health of this population.